Influence of resin cement shade on the color and translucency of ceramic veneers - Daiana Kelly Lopes HERNANDES; Cesar Augusto Galvão ARRAIS; Erick de LIMA; Paulo Francisco CESAR; José Augusto RODRIGUES (Journal of Applied Oral Science)
ABSTRACT Objective This in vitro study evaluated the effect of two different shades of resin cement (RC- A1 and A3) layer on color change, translucency parameter (TP), and chroma of low (LT) and high (HT) translucent reinforced lithium disilicate ceramic laminates. Material and Methods One dual-cured RC (Variolink II, A1- and A3-shade, Ivoclar Vivadent) was applied to 1-mm thick ceramic discs to create thin RC films (100 µm thick) under the ceramics. The RC was exposed to light from a LED curing unit. Color change (ΔE) of ceramic discs was measured according to CIEL*a*b* system with a standard illuminant D65 in reflectance mode in a spectrophotometer, operating in the light range of 360-740 nm, equipped with an integrating sphere. The color difference between black (B) and white (W) background readings was used for TP analysis, while chroma was calculated by the formula C*ab=(a*2+b*2)½. ΔE of 3.3 was set as the threshold of clinically unacceptable. The results were evaluated by two-way ANOVA followed by Tukey's post hoc test. Results HT ceramics showed higher ΔE and higher TP than LT ceramics. A3-shade RC promoted higher ΔE than A1-shade cement, regardless of the ceramic translucency. No significant difference in TP was noted between ceramic discs with A1- and those with A3-shade cement. Ceramic with underlying RC showed lower TP than discs without RC. HT ceramics showed lower chroma than LT ceramics, regardless of the resin cement shade. The presence of A3-shade RC resulted in higher chroma than the presence of A1-shade RC. Conclusions Darker underlying RC layer promoted more pronounced changes in ceramic translucency, chroma, and shade of high translucent ceramic veneers. These differences may not be clinically differentiable.